Group Variable Selection with Oracle Property by Weight-Fused Adaptive Elastic Net Model for Strongly Correlated Data - Fu, Guang-Hui; Zhang, Wen-Ming; Dai, Lin; Fu, Ying-Zi (Communications in statistics. Simulation and computation, 2014)
This paper is the generalization of weight-fused elastic net (Fu and Xu, 2012 ), which performs group variable selection by combining weight-fused LASSO(wfLasso) and elastic net (Zou and Hastie, 2005 ) penalties. In this study, the elastic net penalty is replaced by adaptive elastic net penalty (AdaEnet) (Zou and Zhang, 2009 ), and a new group variable selection algorithm with oracle property (Fan and Li, 2001 ; Zou, 2006 ) is obtained.